Melestarikan Bahasa Daerah Sebagai Identitas Budaya Dalam Pendidikan Sekolah Dasar - karolin Tawasako; Anggun Ramadani; Nurtilawati Nurtilawati; Miftanul Jannah; Herlina Herlina; Kadek Hariana (JURNAL DIKDAS, 2024)
Local language is an important language to preserve in this day and age. This research aims to examine how local identity in each region is maintained in the midst of globalization.  Not only that in the context of education, local language plays a very important role in increasing students' love for local culture. This research uses the literature review method, systematically, using articles that have been obtained from Google Scholar. The result of this study is that preserving local language in elementary schools can form the foundation of national character in the midst of the times to maintain cultural identity so that it does not become extinct.